Characterization and in vivo immunomodulatory effects of a heteropolysaccharide from Rhizopogon rubescens (Tul.) Tul. (November 2022) - Huang, Xinyue; Ding, Huimin; Wang, Qiuyan; Ma, Shixuan; Pan, Daodong; Guo, Yuxing; Tao, Mingxuan
Abstract: This study is the first to isolate and purify the primary polysaccharide fraction (PPRR) from Rhizopogon rubescens (Tul.) Tul using ultrasonic-assisted hot water extraction. PPRR is a heteropolysaccharide composed of glucose, galactose, fucose, rhamnose, mannose, and xylose. After preliminary structural characterization, the main chain of PPRR is →3)- β -D -Glc p -(1→6)- β -D -Glc p -(1→. In vivo experiments showed that PPRR has significant therapeutic effects on the immune damage caused by cyclophosphamide (CPA). In a concentration range of 1–6 mg/mL, PPRR could augment the macrophage phagocytosis function and regulate the abnormal secretion of cytokines such as interleukin (IL)− 2 and interferon (IFN)- γ . Moreover, PPRR could reduce the inhibition of CPA on hematopoiesis of bone marrow and alleviate the damage caused by CPA to the thymus and spleen. These findings suggest that PPRR has the potential to be used as an immunomodulator in the future. Graphical Abstract: ga1 Highlight: Acidic polysaccharide component (named PPRR) was first isolated from Rhizopogon rubescens (Tul.) Tul . The physicochemical properties and structural characteristics of PPRR were preliminarily characterized. PPRR components exhibited good immunomodulatory activity in vivo.